(untitled) (Fiep Bulletin - online, 2015)
This study aims to describe the productions available in the theses database available at Capes (Coordenação de Aperfeiçamento de Pessoal de Nível Superior - Coordination for the Improvement of Higher Education Personnel), for the topics Workers’ Health and Physical Activities. Methodological support was derived from Content Analysis (BARDIN, 1994), and in ninety-eight productions were chosen. It became evident that one of the major problems is related to mental disorders and organic diseases, such as such as ulcers, hypertension, herpes, heart attacks and vascular encephalic strokes. As a preventive measure, it is recommended that the workers engage in continued practice of Physical Activity as a strategy to cope with these morbidities.